Masalah pengumpulan data di Syarikat Perumahan Negara Berhad dalam pemulihan projek perumahan terbengkalai di Selangor - Chan, Ching Yeng (2006)
Project rehabilitation is one of the solutions for the problem of abandoned housing project. Area of study for this research was only focused on the rehabilitation of abandoned housing project by SPNB which more emphasized on the data collection at preliminary stage. This is because; failure of this works will effect the preliminary study process and cause the project to be out from SPNB action. Therefore, this research is aim to study what kind of data collection problem faced by SPNB and how to solve the problems. Method of face to face interview was used to collect primary sources from SPNB executive who placed in project division. Beside that, method of interview by phone was used to collect other primary sources not only from SPNB executive who placed in project division, but also from developers who involve in case study. The rehabilitation project in Selangor which in preliminary stage was choose as case study in this research. However, method of qualitative analysis was used to analyze the primary sources in this study. In short, the analysis result indicate that, SPNB was facing four problems when collecting data in preliminary stage which include problem of developer cooperation, incomplete data from agency involve, unsuitable information form method and legal power problem. These problems not only removed the project out of SPNB rehabilitation action, it also can effect the time which needed to complete the project. Therefore, some of the solution such as campaign realization was suggested to help SPNB overcome these problems. These suggestions not only will help SPNB to smooth the rehabilitation process, but also will help to prevent the project removed from SPNB rehabilitation action.